The Effect of Taxes and Capital Expenditures on Economic Growth The Effects of the COVID-19 Pandemic in Indonesia - Siti Rohima; Abdul Bashir; Mardalena Mardalena; Aning Kesuma Putri (Fakultas Ekonomi, Universitas Bangka Belitung, 2022)
This study aims to determine tax revenues and capital expenditures before and during the COVID-19 pandemic on Indonesia's economic growth. The secondary data from 1980 to 2019 was collected through Badan Pusat Statistik (BPS). This study uses a descriptive quantitative approach. The analysis used in this study is to use the ARDL (Autoregressive Distributed Lag) method. The survey results indicate that tax revenues and capital expenditures in the short and long term have a positive and significant effect on economic growth in Indonesia, which follows the hypothesis of this study. Even tax revenues and capital expenditures have a significant positive impact on fiscal policy to help overcome the pandemic's economic impact. The resulting coefficient value is 0.6705. So that in the long term, an increase in tax revenue of 1 percent will increase economic growth by 0.6705 percent. Furthermore, the long-term capital expenditure variable also has a positive and statistically significant effect, with the resulting coefficient of 0.1743. an increase in capital expenditure of 1 percent will increase economic growth by 0.1743 percent.